Preservice secondary science teachers' teaching proposals to address a socially acute question - Cruz-Lorite, Isabel María; Hervé, Nicolas; Cebrián-Robles, Daniel; Acebal, María del Carmen (My University, 2023)
Teaching about socially acute questions seems beneficial for different aspects of student learning and its use in classrooms can be encouraged by including it in future teachers’ training. This paper analyses teaching proposals made by preservice secondary teachers to address the socially acute question of the dominant model of meat production and consumption. The analysis was carried out in terms of the phases addressed for the inquiry and the conceptions of knowledge and pedagogical strategies adopted. The results show that the proposals are focused on information gathering and analysis, highlighting the controversies (engaged conception of knowledge) with the aim to develop critical thinking by teaching students to argue through the exploration of different positions on the SAQ (critical pedagogical strategies). The educational implications of these results are discussed in this work.
Keywords: Profesores - Formación profesional; Profesores de ciencias - Formación profesional; Enseñanza secundaria - Aspectos sociales; Socially acute questions; Cuestiones socialmente vivas; Preservice secondary science teachers; Profesorado de secundaria en formación inicial; Teaching proposals; Propuestas didácticas